Pengendalian Intern Manajemen Keuangan pada Perusahaan Kontraktor - Maryani, Maryani; Nurfatidah, Sri; Kurniawan, Kurniawan (Jurnal Ilmu Sosial, Manajemen, Akuntansi dan Bisnis, 2024)
This research aims to determine and analyze the project financial management system at CV. Diana Concern. The method used is descriptive qualitative with the type of research being a case study. The data collection technique uses a triangulation process which is carried out by conducting interviews, observation and documentation. The research results show that CV. Diana Concern, which is the object of this research, carries out financial management system activities, especially in project operations, not yet fully using financial system procedures which are the basis for internal control, so it requires improvements to the existing financial system. Where all financial activities are completely handed over to representatives from the subcontractors in each project. Transaction activities that are not recorded on time by ignoring forms or documents accompanying the transaction, as well as implementation orders that are not professionally organized, can cause financial reporting to be inaccurate, not timely and accountable